Immunization: levels, trends and differentials - Boerma, J. Ties; Sommerfelt, A. Elisabeth; Rutstein, Shea O.; Rojas, Guillermo (DHS Comparative Studies No. 1, 1990)
This report presents the results of comparative analysis of immunization coverage (BCG, DPT, polio, and measles) in 21 developing countries. Where possible, DHS data are compared with data from other national surveys and health information systems.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm. The Demographic and Health Surveys (DHS) is a 13-year project to assist government and private agencies in developing countries to conduct national sample surveys on population and maternal and child health. Funded primarily by the United States Agency for International Development (USAID), DHS is administered by the Institute for Resource Development/Macro International Inc. in Columbia, Maryland, USA.